Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Les droits sexuels des personnes handicapées: réflexion sur le développement du droit international - Mona Paré (Genre, Sexualité et Société, 2018)
Interest in the sexuality of persons with disabilities is growing and research improves our understanding of issues in this regard. This leads us to a reflection on the definition of sexual rights in international law, and the way in which sexual rights of persons with disabilities are understood. Examining existing norms leads to the conclusion that despite developments in this area, sexual rights remain largely limited to the field of health, and this has not changed with the adoption of the Convention on the Rights of Persons with Disabilities (CRPD). The limited claims related to these rights during the negotiations of the CRPD is surprising given the significant participation of persons with disabilities. Yet, despite the lack of clarification in relation to the sexual rights of persons with disabilities in the convention, the practice of interpretation of law remains a way to develop international law in this field, particularly through the evolving concept of non-discrimination.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; approches et analyses; capacitisme; cours; discipline; droit; droit des personnes en situation de handicap; droit international; histoire et politique; militance; premier cycle; périodes historiques; ressource en ligne; santé; science politique et droit; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap

Girlhood interrupted: The erasure of Black girls' childhood - Epstein, Rebecca; Blake, Jamilia J.; González, Thalia (Georgetown Law, Center on Poverty and Inequality, 2017)
This groundbreaking study by the Georgetown Law Center on Poverty and Inequality provides—for the first time— data showing that adults view Black girls as less innocent and more adult-like than their white peers, especially in the age range of 5–14. The report builds on similar results that have emerged from studies of adult perceptions of Black boys. In 2014, for example, research by Professor Phillip Goff and colleagues revealed that beginning at the age of 10, Black boys are more likely than their white peers to be misperceived as older, viewed as guilty of suspected crimes, and face police violence if accused of a crime.1 SNAPSHOT OF THE DATA Compared to white girls of the same age, survey participants perceive that • Black girls need less nurturing • Black girls need less protection • Black girls need to be supported less • Black girls need to be comforted less • Black girls are more independent • Black girls know more about adult topics • Black girls know more about sex These results are profound, with far-reaching implications. Our findings reveal a potential contributing factor to the disproportionate rates of punitive treatment in the education and juvenile justice systems for Black girls.
http://arks.princeton.edu/ark:/88435/dsp01tx31qm28z
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; cours; discipline; droit; fem3300; filles noires; genre; identités LGBTQIA2+; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique et droit; sexisme; systèmes d'oppressions; thématiques; états-unis

Sexualized Violence and Colonialism: Reflections on the Inquiry into Missing and Murdered Indigenous Women - Razack, Sherene (Canadian Journal of Women and the Law, 2016)
Introduction to the special isuue of the Canadian Journal of Women and the Law on the "Missing and Murdered Indigenous Women Conference".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminicide; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

“It Happened More Than Once”: Freezing Deaths in Saskatchewan - Razack, Sherene (Canadian Journal of Women and the Law, 2014)
Le présent article analyse les enquêtes et une commission sur des décès par hypothermie en Saskatchewan, au Canada. Il souligne les économies raciales et d’espace liées à ces décès, et il suggère que les relations structurelles propres au colonialisme de peuplement produisent et encouragent les expulsions continues et quotidiennes d’autochtones de la part des colonisateurs, expulsions qui sont inévitablement violentes. La ville coloniale appartient au colonisateur et son occupation est inévitablement récusée par la présence des autochtones dans la ville. L’autochtonité met mal à l’aise, car elle conteste la prétention du colonisateur à la légitimité en remettant en cause une fiction très tenace dans les états coloniaux selon laquelle les peuples autochtones seraient à l’agonie. La pratique qui consiste à repousser les autochtones aux périphéries de la ville vient du besoin des colonisateurs de maintenir les lignes de force des villes coloniales. Aujourd’hui, quand cette pratique est scrutée par le droit, comme ce fut le cas dans l’enquête sur le décès de Neil Stonechild, et dans des enquêtes sur les décès par hypothermie, elle est considérée soit comme le fait de quelques policiers sans vergogne ou encore on la nie carrément. Ce qui demeure dans les registres judiciaires, toutefois, ce sont les économies raciales d’espace dans la ville coloniale et la dévalorisation persistante de la vie autochtone, une dévalorisation que la loi produit et soutient. Dans la première partie, je présente des idées sur les économies raciales et d’espace de la ville coloniale. Dans la deuxième partie, j’étudie le cas du décès de Neil Stonechild, ainsi que la réponse du droit à ce décès, la Commission d’enquête Wright. Dans la troisième partie, j’analyse les enquêtes sur les décès par hypothermie de Rodney Niastus et de Lawrence Wegner, deux jeunes autochtones morts dix ans après Stonechild, et j’explore deux mouvements dans l’espace et le temps : Niastus et Wegner traversant la ville pour trouver la mort dans un champ gelé de la zone nord-ouest, et le cheminement que l’enquête nous invite à faire en nous faisant croire que Niastus et Wegner sont les seuls responsables de leur décès. Dans le panorama des décès d’autochtones en détention en Saskatchewan, y compris en prison, par suicide et à la suite de violents affrontements avec la police, le corps d’un autochtone est un corps qui ne peut être assassiné.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; histoire et politique; hypothermie; justice sociale; meurtre; mort; personnes autochtones; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; violences

Les menaces au droit à l’avortement et à l’autonomie des femmes enceintes - Lemonde, Lucie (Les Cahiers de droit, 2009)
Après un bref survol de l’histoire récente de la criminalisation de l’avortement au Canada, l’auteure présente les divers projets de loi privés touchant d’une façon ou d’une autre le droit à l’avortement, principalement le projet no C-484 sur l’homicide foetal, pour en saisir les conséquences sur le droit canadien et sur l’autonomie des femmes pendant leur grossesse. Ces projets de loi se situent à l’intérieur d’une stratégie des opposants à l’avortement qui a essentiellement pour objet de faire reconnaître en droit canadien un droit à la vie et à la sécurité aux foetus et de remettre en question le libre choix des femmes en la matière. Suit une discussion sur l’instrumentalisation du droit pénal à des fins de contrôle social de questions d’ordre éthique. Le texte se termine par une réflexion concernant l’intérêt de l’État dans la protection des foetus. L’auteure soutient que toute intervention étatique doit se faire dans le respect des droits constitutionnels des femmes, soit leur droit à la vie, à la santé et à la liberté.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; avortement; canada; cours; discipline; droit; droits des femmes*; justice reproductive; justice sociale; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; science politique et droit; sexisme; systèmes d'oppressions; thématiques

Le projet de loi C-3 ou le mythe d’une loi non discriminatrice - Masmoudi, Sakina (Recherches amérindiennes au Québec, 2009)
Le projet de loi C-3, déposé à la Chambre des Communes le 11 mars 2010, fait suite à l’arrêt McIvor du 6 avril 2009 de la Cour d’appel de la Colombie-Britannique (CACB). Ce jugement déclare que les dispositions de la Loi sur les Indiens relatives à l’inscription et à la transmission du statut d’Indien contreviennent à l’article 15 de la Charte canadienne des droits et libertés. Plus précisément, le jugement vise l’article 6 de la Loi sur les Indiens auquel des amendements ont été apportés en 1985 par le projet de loi C-31. À l’époque, de nombreuses voix avaient déploré les discriminations résiduelles de ce projet de loi. Vingt-cinq ans plus tard, le Parlement du Canada se penche enfin sur ces discriminations, s’évertuant à apporter des corrections bien tardives et insuffisantes.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; histoire et politique; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; système pénal; systèmes d'oppressions; thématiques